The Role of Markets, Technology, and Policy in Generating Palm-Oil Demand in Indonesia - Gaskell, Joanne C. (Taylor and Francis, 2015)
Indonesia produces more palm oil and consumes more palm oil per capita than any country in the world. This article examines the processes through which Indonesia has promoted palm-oil consumption and some of the consequences of that promotion. Partial equilibrium modelling shows that Indonesia's remarkable increase in palm-oil consumption since 1985 is not largely attributable to population and income growth. Instead, much of this consumption growth has resulted from substitution away from coconut oil, facilitated by government policies on technology, pricing, distribution, and trade. The switch from coconut oil to palm oil in Indonesia was associated with increased land conversions to agriculture and diminished smallholder competitiveness. Despite lower rates of cooking-oil substitution in the future, simulations suggest that Indonesia's total palm-oil consumption in 2035 will be at least double that of 2010.